(untitled) (Faridpur Medical College Journal, 2020)
Halstedian radical mastectomy is practiced over 40 years as surgical treatment of breast cancer. For the last twenty years, breast conserving surgery (BCS) has been more practiced in the treatment of breast cancer as it provides oncological safety as well as cosmesis. Non palpable breast lesions are being increasingly diagnosed in the recent years as a result of introduction of breast cancer screening, high quality digital mammography and increase in public awareness. Accurate localisation of small, nonpalpable breast lesions is mandatory for accurate surgical management. The purpose of this article is to review the techniques systematically those have been used to locate non-palpable breast lesions which could easily be introduced in Bangladesh. Breast conserving surgery means complete removal of the tumour with a concentric margin of surrounding healthy tissue with maintenance of acceptable cosmesis. It should be followed by radiation therapy (RT) to achieve an acceptably low rate of local recurrence. Breast conserving surgery with radiotherapy has same survival benefit as mastectomy. BCS plus RT provided better outcome than mastectomy for early breast cancer and should be offered as a preferred treatment option. Experience, logistical support, and multidisciplinary approach is key to success. Radiological support with ultrasound or stereotactic localization with wires and /or ultrasound skin marking are key to have accurate wide local excision of non palpable lesions which is gold standard. Other newer techniques such as radio guided occult lesion localisation (ROLL), magnetic seeds, radiofrequency seeds localisation are a feasible and safe method of breast lesion localization as well and gaining popularity slowly. Faridpur Med. Coll. J. Jul 2019;14(2): 93-99